Representative Bureaucracy: Understanding the Correlates of the Lagging Progress of Diversity in Policing. (October 2015) - Morabito, Melissa; Shelley, Tara O'Connor
The domination of policing by White males has long been considered a threat to the legitimacy of the profession, as police agencies have struggled with attracting, retaining, and promoting women and minorities within their agencies for decades. Female and minority representation are hardly stable across agencies with some agencies employing no women or people of color, while others are more representative of the communities they serve. Using a national sample of 1, 478 police jurisdictions, this study further explores the correlates of diversity of women and racial minorities using a framework informed by representative bureaucracy theory. Findings suggest that the same factors are not predictive of representation of women and racial minorities.